2022
DOI: 10.3390/en15093099
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven State Prediction and Analysis of SOFC System Based on Deep Learning Method

Abstract: A solid oxide fuel cell (SOFC) system is a kind of green chemical-energy–electric-energy conversion equipment with broad application prospects. In order to ensure the long-term stable operation of the SOFC power-generation system, prediction and evaluation of the system’s operating state are required. The mechanism of the SOFC system has not been fully revealed, and data-driven single-step prediction is of little value for practical applications. The state-prediction problem can be regarded as a time series pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…LSTM networks were designed to be even better suited than RNNs for classifying, processing, and making predictions based on time series data. In recent years, notable publications revealed that using the LSTM algorithm for the prediction and evaluation of a solid oxide fuel cell (SOFC) system's operating state [137], learning the congestion level of a power distribution system which designates the loading of a distribution feeder [138], and fouling prediction in heat exchangers to avoid inefficiencies and shutdowns [139], provided improved performance compared to the benchmark autoregressive integrated moving average and regression algorithms by between 19.1 and 200% using 629,873, 86,400, and 23,040 real data samples, respectively.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…LSTM networks were designed to be even better suited than RNNs for classifying, processing, and making predictions based on time series data. In recent years, notable publications revealed that using the LSTM algorithm for the prediction and evaluation of a solid oxide fuel cell (SOFC) system's operating state [137], learning the congestion level of a power distribution system which designates the loading of a distribution feeder [138], and fouling prediction in heat exchangers to avoid inefficiencies and shutdowns [139], provided improved performance compared to the benchmark autoregressive integrated moving average and regression algorithms by between 19.1 and 200% using 629,873, 86,400, and 23,040 real data samples, respectively.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…Although fuel cell technology has made significant progress in the past few decades, its commercialization process still faces many challenges, one of which is the issue of fuel cells' short lifespan [8][9][10][11][12]. Specifically, fuel cells will experience a gradual decline in performance during long-term operation.…”
Section: Introductionmentioning
confidence: 99%
“…These perturbation factors pose a challenge for accurately predicting the power output of a SOFC system [24,25]. Currently, in the system environment, the data-driven model of SOFCs often involves gas flow rate at the anode and cathode inlets and outlets, load voltage, and stack temperature [26]. However, there still exist discrepancies between these parameters and the requirements of the entire system.…”
Section: Introductionmentioning
confidence: 99%